The Effectiveness of Forgiveness Meditation Intervention in the Group of Emerging Adult Students - Yohanis Franz La Kahija; Amalia Rahmandani; Salma Salma (Faculty of Psychology, Diponegoro University, 2022)
Evidence of the effectiveness of forgiveness meditation intervention among college students in ‘emergingadulthood’ is still limited. This study aims to examine the effect of forgiveness meditation intervention towardforgiveness, self-forgiveness, forgiveness of others, and forgiveness of situations among college students. Thisstudy used a quasi-experimental one-group pretest-posttest design with measurements follow-up two weeks aftertreatment ended. The subjects were “emerging adulthood”, as many as 9 college students from DiponegoroUniversity, Indonesia (MAge = 20.67; SDAge = 0.5; Female = 77.8%). The results of quantitative analysis usingstatistical test of Wilcoxon Signed Rank Test between pretest and posttest showed a significant increase inforgiveness (z = -2.668, p < .01), self-forgiveness (z = -2.670, p < .01), and forgiveness of situations (z = -2.384,p < .05). Testing between posttest and follow-up were not significant (p > .05). However, the test results betweenpretest and follow-up on these three variables were still significant, z = -2.668, p <.01; z = -2.673, p < .01; and z= -2.388, p < .05, respectively. In contrast, no significant increase in the variable of forgiveness of others (p >.05). The qualitative analysis and further discussions are also presented.